Diagnosis and Management of Borderline Hip Dysplasia and Acetabular Retroversion - Willey, Michael; Holland, Tai; Thomas-Aitken, Holly; Goetz, Jessica E. (The Journal of Hip Surgery, 2018)
Borderline hip dysplasia and acetabular retroversion are common radiographic findings in young individuals with and without hip pain. Orthopaedic surgeons should be knowledgeable about the radiographic findings, diagnosis, and appropriate nonsurgical and surgical treatment of these conditions. Borderline hip dysplasia is generally defined by a lateral center edge angle of Wiberg from 20 to 25° (some define as 18–25°) and is a cause of joint microinstability. The degree of soft tissue laxity can have significant implications for joint stability in patients with borderline hip dysplasia. The most common presenting symptoms are groin pain and lateral hip pain. Acetabular retroversion is defined by radiographic findings of crossover sign, ischial spine sign, and posterior wall sign. Individuals with symptomatic retroversion have a clinical presentation consistent with impingement, groin pain with flexion activities, and less commonly lateral hip pain. Physical therapy has been shown to improve symptoms in a subset of individuals with these conditions. There are multiple recent publications about arthroscopic treatment of patients with borderline hip dysplasia. These reports generally find that good short-term outcomes can be expected when using arthroscopic techniques that include labral preservation/repair and capsular plication. There are limited reports of periacetabular osteotomy as a treatment for borderline hip dysplasia. Publications focusing specifically on surgical treatment of acetabular retroversion are also infrequent. Periacetabular osteotomy has been shown to have superior long-term clinical outcomes to surgical hip dislocation with anterior rim trimming in patients with all three radiographic findings of retroversion. Arthroscopic treatment has been shown to have good short-term outcomes. Future work in the areas of borderline hip dysplasia and acetabular retroversion should focus on reporting long-term clinical follow-up of these surgical treatments and using computation techniques as a tool to determine appropriate surgical and nonsurgical treatment for each individual patient.
Keywords: borderline hip dysplasia; acetabular retroversion; young adult hip conditions